Interaction between clover root weevil and clover root type - Care, D.A.; Crush, J.R.; Hardwick, S.; Nichols, S.N.; Ouyang, L. (New Zealand Plant Protection, 2000)
A slant board experiment investigated the effect of four white clover (Trifolium repens L) root types on tolerance of root feeding by larvae of clover root weevil (Sitona lepidus Gyllenhål) Root damage was determined by image analysis and larval weight gains were measured Differences in root type did not have a major impact on initial damage by clover root weevil However different root types were affected differently by the clover root weevil A clover genotype with long fine roots had more functional root length after larval feeding than genotypes with different root types